Using the trigonometric identity (sinx)^2 + (cosx)^2 = 1, show that (secx)^2 = (tanx)^2 + 1 is also a trigonometric identity.

We can divide by (cosx)^2 across the identity (sinx)^2 + (cosx)^2 = 1 (which can be derived from properties of the unit circle and a bit of Pythagoras’ theorem) to achieve

[(sinx)^2 / (cosx)^2] + [(cosx)^2 / (cosx)^2] = [1 / (cosx)^2]

Which leaves us with our desired identity

(tanx)^2 + 1 (secx)^2 = 1

Answered by Annie B. Maths tutor

3102 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate f(x) with respect to x. Find the stationary value and state if it is a maxima, minima or point of inflection f(x) = 6x^3 + 2x^2 + 1


How do I solve equations like 3sin^2(x) - 2cos(x) = 2


Given that sin(x)^2 + cos(x)^2 = 1, show that sec(x)^2 - tan(x)^2 = 1 (2 marks). Hence solve for x: tan(x)^2 + cos(x) = 1, x ≠ (2n + 1)π and -2π < x =< 2π(3 marks)


Find the stationary points of the equation. f(x)=3x^2+4x.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences